2006
DOI: 10.1177/1077801205277358
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Sexual Violence Against College Women

Abstract: This investigation examined college women's experiences with unwanted sexual contact. Participants completed a questionnaire assessing the incidence of various types of forced sexual contact the women had experienced since enrolling in college. Demographic and situational variables associated with these incidents of sexual violence were also obtained. It was observed that since enrolling in college, 27% of the sample had experienced unwanted sexual contact ranging from kissing and petting to oral, anal, or vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
167
1
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(208 citation statements)
references
References 26 publications
15
167
1
16
Order By: Relevance
“…For example, if the CSA experiences of White women were typically less severe than those of African American and Hispanic women, this disparity could account for the observed ethnic difference in the impact of CSA on the likelihood of subsequent revictimization. In support of this hypothesis, Gross, Winslett, Roberts, and Gohm (2006) found that compared with White women, African American women reported higher rates of adult rape involving the use of physical force by the perpetrator.…”
Section: Ethnic Differences In Sexual Victimization and Revictimizationsupporting
confidence: 67%
“…For example, if the CSA experiences of White women were typically less severe than those of African American and Hispanic women, this disparity could account for the observed ethnic difference in the impact of CSA on the likelihood of subsequent revictimization. In support of this hypothesis, Gross, Winslett, Roberts, and Gohm (2006) found that compared with White women, African American women reported higher rates of adult rape involving the use of physical force by the perpetrator.…”
Section: Ethnic Differences In Sexual Victimization and Revictimizationsupporting
confidence: 67%
“…Diversas investigaciones realizadas tanto a nivel internacional como en el contexto español revelan la persistencia de los desequilibrios y desigualdades relacionados con el género en el ámbito universitario (Edwards, Desai, Gidycz, & Vanwynsberghe, 2009;Gross, Winslett, Roberts, & Ghom, 2006;López, & Pérez, 2014). Si bien en España existe un marco legal favorable que ha permitido la reversión de una ventaja femenina con relación a la presencia masculina en la universidad, cuestión que ha sido observada y analizada por científicos y académicos sociales (véase Buchmann, DiPrete, & McDaniel, 2008;Goldin, Katz, & Kuziemko, 2006), las mujeres aún se enfrentan a una serie de barreras relacionadas con el género para lograr el éxito en carreras dominadas por los hombres como las ingenierías, que son catalogadas por la sociedad como carreras masculinas y competitivas (Stonyer, 2002).…”
Section: Introductionunclassified
“…The prevalence of first victimization of completed rape (defined as forced penetration and completed alcohol-or-drug-facilitated penetration) among females is 78.7% occurring before the age of 25 years, with 38.3% of completed rapes occurring during the age associated with college, 18-24 years (Black et., 2011). Supporting the NISVS data, various studies have shown that more than one in four college women report being forced to have sexual intercourse at some point in their lifetimes (Gidycz, Orchowski, King, & Rich, 2008;Gross, Winslett, Roberts, & Gohm, 2006;Untied, Orchowski, Mastroleo, & Gidycz, 2012). The estimated sexual violence reported by men is lower than that experienced by women.…”
Section: Introductionmentioning
confidence: 67%